Equipment failures and their contribution to industrial incidents and accidents in the manufacturing industry. Issue 1 (2nd January 2016) - Bourassa, Dominic; Gauthier, François; Abdul-Nour, Georges
Abstract : Accidental events in manufacturing industries can be caused by many factors, including work methods, lack of training, equipment design, maintenance and reliability. This study is aimed at determining the contribution of failures of commonly used industrial equipment, such as machines, tools and material handling equipment, to the chain of causality of industrial accidents and incidents. Based on a case study which aimed at the analysis of an existing pulp and paper company's accident database, this paper examines the number, type and gravity of the failures involved in these events and their causes. Results from this study show that equipment failures had a major effect on the number and severity of accidents accounted for in the database: 272 out of 773 accidental events were related to equipment failure, where 13 of them had direct human consequences. Failures that contributed directly or indirectly to these events are analyzed.